Legal Analysis of Breach of Default in Paylater Services as Part of Financial Technology Development in Indonesia - Anggawira Anggawira; Rahmat Dwi Putranto; Brigita P. Manohara (Law Development Journal, 2026)
The development of financial technology (fintech) has driven significant changes in people's transaction patterns, one of which is through paylater services that offer easy access to instant financing. However, this convenience also poses legal risks, particularly related to default due to user failure to fulfill payment obligations. This study aims to analyze the application of the default concept in paylater services, the effectiveness of the regulations governing it, and the need for legal adaptation to address the characteristics of digital transactions. The method used is normative legal research with a statutory and conceptual approach, as well as qualitative data analysis. The legal sources used include the Civil Code, Law Number 8 of 1999 concerning Consumer Protection, and Financial Services Authority Regulation Number 10/POJK.05/2022. The results show that the default concept remains relevant, but requires adjustments in its application, particularly in the aspects of electronic evidence and legal responsibility in digital systems. Furthermore, although regulations have established the principles of prudence and consumer protection, implementation challenges remain, such as weak identity verification and oversight.